PECULIARITIES OF TREATMENT OF EPILEPSY AT GIRLS AND WOMEN - O. A. Pylaeva; K. Yu. Мukhin; D. V. Моrozov (Русский журнал детской неврологии, 2015)
The epilepsy treatment is to be based on existing general principles and standards of therapy with differential approach to each patient. Besides peculiarities of treatment of different types of seizures and forms of epilepsy there are also differential approaches to special groups of patients. To one of such groups are referred to women of reproductive age. These patients are referred to special group of risk due to the development of certain side effects of antiepileptic drugs (АED). This article focuses in details on peculiarities of treatment of women of reproductive age with epilepsy with accent made on tolerability and safety of the antiepileptic therapy. It is necessary to take into consideration, that at women neuroendocrinal disorders can be caused both by the disease itself – epilepsy (in such case disorders depend on the starting age, form of epilepsy, focal localization, duration of disorder and other factors, referred to the disease), as well as by the undertaken therapy. The articlehereunder considers only issues, referred to the treatment, i. e. AED side effects and its input in the decrease of life quality of women with epilepsy. As women’s reproductive function starts forming long ago before childbearing age, it is necessary for this category to comprise not only women and adolescents, but girls as well. Notwithstanding the fact that so called benign forms of epilepsy pass before the pubescence period (idiopathic focal epilepsies, several forms of idiopathic generalized epilepsy), in many cases the epilepsy, which has started in childhood, continues in the adult age as well. In the same time there can be possible remote negative consequences of the antiepileptic therapy, which can show at a woman of a reproductive age. The data, given in the article, witnesses the need of the right AED selection at women of reproductive age, suffering from epilepsy. The AED should be selected not only depending on the form of the epilepsy and on the kind of seizures, but also provided its influence on the neuroen docrinal status of a woman, as well as on its influence on the reproductive system. With that it should be kept in mind that the reproductive function is very important not only from the point of view of woman’s health, but also from the point of view of her family and social status. If possible, women and men of reproductive age (including adolescents) should avoid AED with strong induction of the fermentative system of the liver (all barbiturates, hydantoins, carbamazepine), women should also avoid AED, containing valproic acid. In such cases the priority can be given to new AED, not affecting neuroendocrinal functions and the reproductive system.